The Characteristics of Benign Prostatic Hyperplasia (BPH) in Rumah Sakit Umum Haji Medan - Public Health and Epidemiology - Dr.dr Shahrul Rahman, Sp.PD., Finasim Rahman, Sp.PD., Finasim (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The Characteristics of Benign Prostatic Hyperplasia (BPH) in Rumah Sakit Umum Haji Medan - Public Health and Epidemiology